Resilience-oriented navigation and negotiation processes of at-risk students at upper-secondary schools: a mixed-methods case study - Kassis, Maria; Widmer, Franziska; Düggeli, Albert; Kassis, Wassilis; Preite, Luca (Frontiers in Education, 2025)
IntroductionFrom January 2020 to June 2023, we investigated the success pathways on how at-risk students from low-income families with migration backgrounds and unstable grades could graduate from upper secondary school in a German-speaking region of Switzerland by attending an Academic Advancement Programme (AAP). Considering successful school resilience, we applied metaphor of navigation (access to resources) and negotiation (child-centered interactions with the environment providing services) to school settings.MethodsWe conducted a longitudinal (10th to 12th grades) mixed-methods case study to analyze the data of at-risk students. Based on our research question, we selected three participants (two young women and one young man) from the program to examine how at-risk young people navigate and negotiate their way through a program designed to help them achieve an upper-secondary qualification. At various measurement points, we used both qualitative (guided interviews, observations, and field notes) and quantitative (standardized questionnaires) methods to gain insight into how young people perceive and use the AAP and how they develop in terms of school performance.ResultsThe results indicate that navigation and negotiation processes vary but that overall, grades guide the process. Self-efficacy can be achieved if teachers are adaptable and learning strategies can be developed. Relationships with teachers and peers were central to the learning process. Additionally, it was crucial for at-risk youth to have various graduation options at various levels.DiscussionOur study highlights the need for systemic and customized support to promote equitable schooling practices, emphasizing that students’ individual activities, access to resources, and human relationships are crucial for resilience.